The effect of neoadjuvant imatinib therapy on outcome and survival in rectal gastrointestinal stromal tumors: A multiinstitutional study. Issue 7 (29th July 2021) - Yang, Wenchang; Liu, Qian; Lin, Guole; Zhang, Bo; Cao, Hui; Zhao, Yan; Xia, Lijian; Feng, Fan; Xiong, Zhiguo; Hu, Junbo; Ye, Yingjiang; Tao, Kaixiong; et al.
Abstract: Background and Objectives: This study aimed to characterize the efficacy of neoadjuvant imatinib in rectal gastrointestinal stromal tumors (GISTs) and the prognostic characteristics of patients after surgery. Methods: Patients with rectal GISTs who received neoadjuvant imatinib between 2000 and 2019 were selected from 11 large‐scale tertiary hospitals in China. The best response to neoadjuvant imatinib was assessed. Propensity score matching (PSM) was conducted to reduce confounders. Recurrence free survival (RFS) and overall survival (OS) were estimated using Kaplan–Meier method. Results: Of the 100 patients, 75, 18, and 7 had a partial response (PR), stable disease (SD), and progressive disease (PD), respectively. The median tumor size decreased from 5 cm before treatment to 4 cm after treatment ( p  < 0.001). A total of 31 patients underwent genetic testing after surgery; 23 of patients with exon 11 mutation had PR and 2 had SD. One of the patients with exon 9 mutation had PR, 2 had SD, and 1 had PD. Two patients with the wild type GIST had PD. A total of 86 patients underwent surgery of which 85 underwent complete resection; 72 underwent anal preservation and 40 underwent local excision (LE). After PSM, patients who received neoadjuvant therapy had higher rates of LE ( p  = 0.001) and anal preservation ( p  = 0.033) than those of patients without neoadjuvant therapy. The median follow‐up time was 37 months. Nine patients experienced recurrence and one patient died. The 3‐year RFS and OS rates were 95.0% and 100%, respectively. After PSM, we found that there was no significant difference in RFS between patients who received or did not receive neoadjuvant therapy ( p  = 0.623). Univariate analysis showed postneoadjuvant tumor size ( p  = 0.469) and mitotic count ( p  = 0.294) were not associated with the RFS in patients who received neoadjuvant imatinib. Conclusions: Neoadjuvant imatinib can shrink rectal GIST size, increasing the possibility of complete resection and anal preservation. Further studies are warranted to understand the long‐term outcomes of rectal GISTs in patients receiving neoadjuvant imatinib.